CHIELD: the causal hypotheses in evolutionary linguistics database. Issue 2 (16th April 2020) - Roberts, Seán G; Killin, Anton; Deb, Angarika; Sheard, Catherine; Greenhill, Simon J; Sinnemäki, Kaius; Segovia-Martín, José; Nölle, Jonas; Berdicevskis, Aleksandrs; Humphreys-Balkwill, Archie; Little, Hannah; Opie, Christopher; et al.
Abstract: Language is one of the most complex of human traits. There are many hypotheses about how it originated, what factors shaped its diversity, and what ongoing processes drive how it changes. We present the Causal Hypotheses in Evolutionary Linguistics Database (CHIELD, https://chield.excd.org/ ), a tool for expressing, exploring, and evaluating hypotheses. It allows researchers to integrate multiple theories into a coherent narrative, helping to design future research. We present design goals, a formal specification, and an implementation for this database. Source code is freely available for other fields to take advantage of this tool. Some initial results are presented, including identifying conflicts in theories about gossip and ritual, comparing hypotheses relating population size and morphological complexity, and an author relation network.